Новаторство малых пьес А.П. Чехова (этюд "На большой дороге") - Полежаєва, Тетяна Вікторівна; Polezhaieva, Tetiana V. (Дніпропетровський університет імені Альфреда Нобеля, 2013)
Статья фиксирует поверхностные суждения в литературоведении об одноактной пьесе Чехова “На большой дороге”, показывает наличие в ней собственно “чеховской новаторской поэтики” и авторскую критику романтического героя. Стаття фіксує поверхові судження в літературознавстві про одноактну п’єсу Чехова “На великій дорозі”, показує, що в ній має місце власне “чеховська новаторська поетика” та авторська критика романтичного героя. The article fixes superficial judgements in literary criticism about the one-acter of Chechov “On the large road”, shows that in it takes place own “Chekhov’s innovative poetics” and author criticism of romantic hero.

The article fixes superficial judgements in literary criticism about the one-acter of Chechov «On the large road», shows that in it takes place own «Chekhov’s innovative poetics» and author criticism of romantic hero.
Іnnovative of A. P. Chekhov’s small plays (“On the large road”)
Keywords: Чехов; малая пьеса; тип конфликта; сюжет; Chechov; small play; type of konflikt; subject; implication; criticism of romantic hero; image-background; images-circumstances